ANALISIS KESALAHAN PLEONASME DAN AMBIGUITAS PADA ESAI SIAPKAH HADAPI PERUBAHAN KURIKULUM? KARYA FIRDA HAYATUNNISA - Widowati, Jesika; Casim, Casim (DIALEKTIKA JURNAL PENDIDIKAN BAHASA INDONESIA, 2025)
One of the language errors in essays is semantic errors including symptoms of pleonasm and ambiguity. Essays written by authors may contain errors even though they have been published. The purpose of this study is to describe and discuss pleonasm and ambiguity errors in the essay Siapkah Hadapi Perubahan Kurikulum? by Firda Hayatunnisa. The method applied in this study is a descriptive qualitative approach. The data applied in this study is the essay Siapkah Hadapi Perubahan Kurikulum? by Firda Hayatunnisa. The reading technique is carried out by approaching reading the entire contents of the essay Siapkah Hadapi Perubahan Kurikulum? by Firda Hayatunnisa carefully and repeatedly. Meanwhile, the note-taking technique is applied by noting every language error related to semantics, including symptoms of pleonasm and ambiguity. The results of the analysis of two semantic errors include; (1) symptoms of pleonasm in the form of words: then, again, what happened and this, next, also, want, able, use and utilize, good and correct, capable and qualified, on, which for, qualified, and desired, and (2) ambiguity in the form of phrases: previous curriculum, students were no longer forced to study subjects that were not their main interests, in the words teacher only as a facilitator and provider of direction, and in the phrase all kinds of information. semantic errors in symptoms of pleonasm and ambiguity in the essay Siapkah Hadapi Perubahan Kurikulum? Firda Hayatunnisa's work predominantly occurs in errors of symptoms of pleonasm. Keywords: pleonasm, ambiguity, and essays